Predicting the Duration of Chloroquine, Mefloquine, Halfantrine and Artesunate for Blood Schizonticidal Effect using Mathematical Models of Malaria with Immune Response - Kitisin, Nataphan; Suavansri, Panit (Journal of Basic and Applied Pharmacology, 2017)
This paper focuses on the mathematical model of the death rate of malaria parasite due to chloroquine, mefloquine, halfantrine and artesunate together with the immune response in order to determine the treatment period. The basic knowledge of probabilities, pharmacology, microbiology, medicines, physics and chemistry are used to support this model and hypotheses. One of the hypotheses is the convective theory used for calculating and converting the flow rate of drug molecules with respect to malaria parasite into the death rate of malaria parasite. Other instruments are five probability factors, which the authors use to determine the efficiency of the drugs parasites. Applied this model of death rate with normal malaria model and take into account of the immune response, the treatment durations result in the ranges between 1 to 15 days and are compatible with the real clinical data.